ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PELAKSANAAN PEKA (PENGAMATAN KESELAMATAN KERJA) DALAM PENGENDALIAN KECELAKAAN KERJA DI AREA MAIN GATHERING STATION PT X CEPU - Muhammad Faizal Reza Ferdiniko; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on data from the US Bureau of Labor Statistics (2007) there are approximately 5 cases of accidents and occupational diseases each year for every 100 workers (5 cases / 100 workers) or a total of about 4 million dollars every year. PEKA PT X is a program to record unsafe condition, unsafe act and near misses in the workplace PT X.The problem of implementation PEKA is PEKA form has been run each month, but the behavior of workers and in part of HSSE crew to fill out a PEKA form in finding unsafe condition, unsafe act, and near misses are lacking so that the incidence of unsafe condition, unsafe act, and near misses yet decrease. Implementation of PEKA form has been running every month but the interest of workers and HSSE crew to fill out a form PEKA still less so that the incidence of unsafe condition, unsafe act, and near misses has not decreased. This study aims to determine the factors that may affect the implementation of PEKA in Main Gathering Station PT X Cepu. This research is a descriptive qualitative with indepth interviews. The subjects of this study amounted to 6 people as the key informants and 2 as an triangulation informant. The results showed key informants already know the definition, function, purpose and entitled workers to fill PEKA, but some key informants did not know PEKA accountability. Attitudes and skills of key informants already know how charging PEKA, but there has been no interest in workers. Availability of PEKA form in the workplace. Socialization is held when the safety induction, safety briefing, safety talk, and HSE training. The regulation and reward has been existing, but punishment has not been carried out. The main informant argued that there has been no follow-up about PEKA. X company need to provide socialization PEKA regularly in order to avoid misunderstandings between the function of X company and workers. Follow-up and real evidence of PEKA also needed for all workers know about PEKA process.